Evaluating silicone breast implant rupture with photon-counting CT and volumetric silicone maps - Todd C. Soesbe, PhD; Richard W. Ahn, MD, PhD; Liqiang Ren, PhD; Stephen Seiler, MD; Andres Abadia, PhD; Kristina A. Hallam, PhD; Matthew A. Lewis, PhD (Radiology Case Reports, 2024)
We present a case of an 81-year-old woman who presented to the emergency department with bleeding from a right breast wound. The patient had prior imaging suggestive of bilateral silicone implant rupture and a history of low tolerance for MRI scans. Ultrasound imaging in the emergency setting showed findings in the right breast suggestive of a fistula with free silicone and hematoma. A subsequent photon-counting CT scan with custom silicone-specific segmentation allowed differentiation of silicone from hematoma, provided anatomic assessment and location of the fistula, and revealed bilateral silicone-induced lymphadenopathy.